2015
DOI: 10.1253/circj.cj-14-1290
|View full text |Cite
|
Sign up to set email alerts
|

QTc Interval Prolongation Predicts Arrhythmia Recurrence After Catheter Ablation of Atrial Fibrillation in Patients With Hypertrophic Cardiomyopathy

Abstract: Background:In hypertrophic cardiomyopathy (HCM) patients complicated with atrial fibrillation (AF), catheter ablation has been recommended as a treatment option. Meanwhile, prolongation of QTc interval has been linked to an increased AF incidence in the general population and to poor outcomes in HCM patients. However, whether QTc prolongation predicts arrhythmia recurrence after AF ablation in the HCM population remains unknown. Methods and Results:Thirty-nine HCM patients undergoing primary AF ablation were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
5
17
0
Order By: Relevance
“…Some predictors including Age, NYHA functional class, LAD, AF duration, QTc prolongation, LV diastolic dysfunction, or LV outflow obstruction have been reported by the previous study 9,10,12,14,15 . In our data, except for LAD ≥ 50 mm (HR 3.319, 95% CI, 1.469‐7.499; P = .004) and NYHA functional class ≥ III (HR 2.422, 95% CI, 1.032‐5.685; P = .042), Female (HR 2.358, 95% CI, 1.151‐4.831; P = .019) was proven to be a predictor of AF recurrences after multiple procedures, it seems that females are older than males with a mean age of 63.6 ± 9.1 years vs 59.4 ± 10.1 years in males ( P value = .025) in our data.…”
Section: Discussionsupporting
confidence: 71%
“…Some predictors including Age, NYHA functional class, LAD, AF duration, QTc prolongation, LV diastolic dysfunction, or LV outflow obstruction have been reported by the previous study 9,10,12,14,15 . In our data, except for LAD ≥ 50 mm (HR 3.319, 95% CI, 1.469‐7.499; P = .004) and NYHA functional class ≥ III (HR 2.422, 95% CI, 1.032‐5.685; P = .042), Female (HR 2.358, 95% CI, 1.151‐4.831; P = .019) was proven to be a predictor of AF recurrences after multiple procedures, it seems that females are older than males with a mean age of 63.6 ± 9.1 years vs 59.4 ± 10.1 years in males ( P value = .025) in our data.…”
Section: Discussionsupporting
confidence: 71%
“…fQRS is a convenient marker of myocardial scarring on 12‐lead ECG and has been shown to predict cardiac events, classically in patients with myocardial infarction as well as nonischemic cardiomyopathy, arrhythmogenic right ventricular dysplasia, Brugada syndrome, and HCM. In our series, 60% of patients presented with fQRS at baseline, which is similar to the prevalence previously reported . In HCM, fQRS has been associated with ventricular arrhythmias, heart failure progression, and SCD .…”
Section: Discussionsupporting
confidence: 89%
“…Given the strong ties between AF and HCM, we investigated the impact of QTc interval on the outcomes of AF ablation in HCM patients. Our preliminary study was the first to demonstrate that the preprocedural QTc interval is an independent predictor of arrhythmia recurrence in HCM patients undergoing AF ablation . The present study, which includes a three‐fold larger sample size, confirmed the previous findings.…”
Section: Discussionsupporting
confidence: 88%
“…Of these, 177 were excluded as they were either duplicates or deemed unsuitable for the purpose of the meta-analysis (editorials, letters, reviews or case reports). The remaining 32 studies were carefully screened and after analysis of their abstracts and/or full-text only [14][15][16][17][18][19][20][21][22][23][24][25][26][27] (one was a conference abstract 22 ) were considered adequate for inclusion in the systematic review (figure 1). Of these, only six studies, 16 19 22-25 provided enough details to be included in the meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…17 18 24-27 In two studies, persistent AF was also associated with worse procedural outcomes (OR=7.7, 95% CI 1.13 to 50, p=0.02 20 and OR=2.58, 95% CI 1.11 to 6.05, p=0.028 21 ). Other predictors of relapse were identified separately in single studies: age and New York Heart Association (NYHA) class, 18 left atrial pressure and left ventricle (LV) outflow tract obstruction, 24 AF duration in months and E/E 0 , 25 and corrected QT interval (QTc) duration 27 (table 4).…”
Section: Predictors Of Procedural Successmentioning
confidence: 99%